THE DRIVERS FOR ACCEPTANCE OF NON-CREDIT CARD INSTALMENT SERVICES - Dara Safira, Indira
The boom of Peer-to-Peer Lending (P2PL) Fintech in Indonesia has attracted the attention of researchers towards one of its features, which is non-credit card installment services. Non-credit card instalment services in Indonesia is relatively new and is still low in use because Indonesians tend to use other methods rather than non-credit card instalment services. Because of that, it raises basic questions about the appearance of this services, is the presence of non-credit card instalment acceptable to consumers as a technological advance that must exist in this modern era. This paper presents an empirical investigation to determine the drivers of user acceptance of the non-credit card installment services in Indonesia. The main purpose was to find out variables which affect the acceptance level of people in terms of the non-credit card installment services. This research adapted a model that designed by Venkatesh, et al. which is UTAUT 2 and has seven key constructs that influence behavioral intention to use a technology and actual usage of the technology in the context of consumers. Moreover, previous studies of technology acceptance emphasized the importance of perceived security in the acceptance of new technology context, so this study expanded the model with one more external factor, perceived security. Thus, this study considers the effects of eight variables on acceptance of non-credit card installment services. Furthermore, the market segmentation for each of non-credit card instalment services are still unclear. Hence, this research is conducted to know the segments for each of non-credit card instalment services, so that there will be no overlap between one of the services’ market toward another. This study used questionnaire that distributed online through google form. The respondents limited to people that aged between 19 until 54 years old and live in Jakarta or Bandung. Total of 297 respondents have been responded to the questionnaire. Data analysis techniques were carried out using Partial Least Square (PLS)-SEM analysis. The results that found in this study are performance expectancy, effort expectancy, social influences, hedonic motivation, price value, habit have significant effect on behavioral intention to use. While, the facilitating conditions and perceived security do not have a significant effect on behavioral intention to use non-credit card installment services. Moreover, behavior intention to use is proven has significant positive effect toward the actual use. Lastly, each of non-credit card instalment services have a different market segmentation. So, there is no overlap between each of services’ market. The result of this study will be used as an evaluation material and also, to accelerate the development of non-credit card installment services in Indonesia.